Braunwald's Heart Disease. vol. 1 : a Textbook of Cardiovascular Medicine - Libby, Peter (Saunders, 2008)
Dr. Braunwald\'s masterwork returns ... bringing you the definitive guidance you need to overcome any challenge in clinical cardiology today, using the best approaches available! Hundreds of world authorities, many of them new to this edition, synthesize all of the recent developments that are revolutionizing practice - from the newest findings in molecular biology and genetics to the latest imaging modalities, interventional procedures, and medications. The expertise of the book\'s contributors, the scope of its coverage, and its richly illustrated, user-friendly format all make this the ultimate reference for the practicing cardiologist.Locate the answers you need fast, thanks to a user-friendly, full-color design, complete with more than 1,500 color illustrations.Glean clinically actionable information quickly with Clinical Practice Points in every chapter.Incorporate all of the text\'s illustrations into your own PowerPoint® presentations with the bonus CD-ROM.Apply the latest knowledge in your field with 7 new chapters on Acute Heart Failure · Device Therapy of Heart Failure · Emerging Therapies for Heart Failure · Complementary and Alternative Approaches to Management · Prevention and Management of Stroke · Hypertrophic Cardiomyopathy · and Coronary Arteriography Guidelines.Implement the most current, reliable practices thanks to meticulous revisions and updates throughout the book.Get fresh perspectives on your practice with contributions from more than 20 brand-new authors.
Keywords: kardiologie; Cardiology; kardiovaskulární nemoci; Cardiovascular Diseases; Heart Diseases; nemoci srdce